Exergy characteristics of biogas power plants - Мазуренко, Антон Станиславович; Денисова, Алла Евсеевна; Климчук, Александр Андреевич; Нго, Минь Хиеу; Котов, Павел Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
The technique of an exergy analysis concerning various circuits of biogas units, which allow replacing traditional energy resources and improving environmental conditions, has been presented. The heat balances of biogas units were proposed, and analysis of their effectiveness was made. The comparison of different cycle parameters of various biogas units (i.e. a combustion turbine unit, a combined cycle gas turbine unit with gas discharges into the boiler and a combined cycle gas turbine with a high-temperature vapor generator and a reheating stage) was made, and the comparison of their exergy characteristics was carried out. The exergy analysis has shown that the cycle of biogas CCGT (combined cycle gas turbine) with a reheating stage and using a high-pressure steam generator is the most effective, that can be explained by the fact that the temperature energy proportions of combustion products, accounting for the steam cycle and the gas cycle are approximately equal, comparing to conventional combined cycle gas turbine units.